Mandatory HPV Vaccination; Opportunity to Save Lives, Improve Readiness and Cut Costs. Issue 11 (12th June 2021) - Sitler, Collin A; Weir, Larissa F; Keyser, Erin A; Casablanca, Yovanni; Hope, Erica
ABSTRACT: Human papillomavirus (HPV) is the most common sexually transmitted infection (STI) in the U.S. military and accounts for more healthcare visits than the next two most common STIs combined. Human papillomavirus is preventable with a safe, effective, prophylactic vaccine that has been available since 2006, yet vaccination rates remain low. The vaccine is approved for females and males aged 9-45 years for prevention of HPV-related dysplasia and cancers. Although it is recommended by the Centers for Disease Control and Prevention (CDC)'s Advisory Committee on Immunization Practices (ACIP), it is not part of the U.S. military's mandatory vaccine list. Human papillomavirus does not just affect female service members—male service members have a higher reported seropositive rate than their civilian counterparts and can develop oropharyngeal, anal, or penile cancers as sequelae of HPV. Oropharyngeal cancer, more common in males, is the fastest growing and most prevalent HPV-related cancer in the USA. Several countries, such as Australia and Sweden, have successfully implemented mandatory vaccine programs and have seen rates of HPV-related diseases, including cancer, decline significantly. Some models project that cervical cancer, which is the fifth-most common cancer in active duty women, will be eliminated in the next 20 years as a result of mandatory vaccination programs. Between higher seropositive rates and lack of widespread vaccination, HPV dysplasia and cancer result in lost work time, decreased force readiness, negative monetary implications, and even separation from service. With more than half of the 1.3 million service members in the catch-up vaccination age range of less than 26 years of age, we are poised to have a profound impact through mandatory active duty service member vaccination. Although multiple strategies for improving vaccination rates have been proposed, mandatory vaccination would be in line with current joint service policy that requires all ACIP-recommended vaccines. It is time to update the joint service guidelines and add HPV vaccine to the list of mandatory vaccines.